2016
DOI: 10.1007/s12639-015-0713-x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Toxoplasma gondii in small ruminants in Chennai using PCR and modified direct agglutination test

Abstract: A total of 193 sera samples, along with tissues (lung, heart, and brain) collected from 136 sheep and 57 goats from the Corporation slaughter house, Madras Veterinary College teaching hospital, and private mutton shops from Chennai were tested for Toxoplasma gondii.All the sera samples were tested using modified direct agglutination test. Of the 193 sera samples, 57 (29.5 %) had a minimum titre of 1:20, with 30.14 % (41/136) of sheep and 28.07 % (16/57) of goats being seropositive. Tissue samples from all 193 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 20 publications
1
3
0
1
Order By: Relevance
“…A low prevalence of 7% recorded in the pigs in current study was comparable with the prevalence reported in sheep, goat (4–6%) and poultry (5%) in India [2, 27, 33]. This low prevalence could be attributed to false negative results due to use of small amount of tissue sample (200 ul) for extracting DNA in the current study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A low prevalence of 7% recorded in the pigs in current study was comparable with the prevalence reported in sheep, goat (4–6%) and poultry (5%) in India [2, 27, 33]. This low prevalence could be attributed to false negative results due to use of small amount of tissue sample (200 ul) for extracting DNA in the current study.…”
Section: Discussionsupporting
confidence: 82%
“…Previously, DNA of T. gondii was detected in other meat producing animals (e.g. sheep, goat and poultry) from India [2, 27, 33]. Methods for detection of T. gondii or its DNA include bio-assays, tachyzoite culture, immunohistochemistry and PCR [29]; all but PCR are labour intensive and time consuming.…”
Section: Discussionmentioning
confidence: 99%
“…Samples and sampling area 14 number titre (136 numbers of sheep and 57 numbers of goats) of samples showed positivity by MDAT at 1:20 titre by MDAT out of 193 samples (either of lung, brain and heart) used for our previous study (Satbige et al 2016) were utilized for the isolation and genotyping studies in T. gondii free BALB/c mice (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 33% of the global population has been identified as infected with toxoplasmosis [51], and drinking unpasteurized and unboiled sheep and goat milk has been identified as the cause of human toxoplasmosis [48,[52][53][54]. Food animals, goats, and sheep (small ruminants) are the most highly afflicted species among mammals with infection of T. gondii [55], and they are potential pathways for human disease transmission [56].…”
Section: Introductionmentioning
confidence: 99%